2021
DOI: 10.1007/s11845-020-02455-5
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of risk factors of in-hospital death due to COVID-19: a case-control study in Rasht, Iran

Abstract: Background Identifying the non-survived patients' characteristics compared to survived subjects and introducing the critical risk factors of COVID-19 mortality would help enhance patients' prognosis and treatment. Methods In the current case-control study, medical records of 103 non-survived COVID-19 patients (cases) and 147 sexmatched survivors (controls) who admitted to Razi University Hospital in Rasht, Guilan, Northern Iran from April 21 to August 21, 2020, were explored. Data on demographic, anthropometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
(107 reference statements)
0
12
0
Order By: Relevance
“…A previous study in Iran demonstrated that obesity, higher levels of CRP, blood sugar, D-dimer, and lipid markers are predictive factors of COVID-19-related mortality. 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study in Iran demonstrated that obesity, higher levels of CRP, blood sugar, D-dimer, and lipid markers are predictive factors of COVID-19-related mortality. 4 …”
Section: Introductionmentioning
confidence: 99%
“…A previous study in Iran demonstrated that obesity, higher levels of CRP, blood sugar, D-dimer, and lipid markers are predictive factors of COVID-19-related mortality. 4 In humans, COVID-19, caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), progresses rapidly to induce acute respiratory distress syndrome (ARDS), leading to the appearance of symptoms. 5 During ARDS due to COVID-19, changes to the host's immunological status occur, including neutropenia, dendritic cell depletion, natural killer cell depletion, decreased T (T CD4þ and CD8þ) and B lymphocytes, and increased proinflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective case-control study conducted in Iran included 250 COVID-19 patients [ 23 ]. No significant difference on HDL-C levels was observed between 103 deceased and 147 survived patients.…”
Section: Resultsmentioning
confidence: 99%
“…No significant difference on HDL-C levels was observed between 103 deceased and 147 survived patients. Of note, higher levels of TCHOL [Odds ratio (OR) = 2.55; 95% CI = 1.19–5.45] and LDL (OR = 2.27; 95% CI = 1.07–4.79) as well as elevated triglycerides (OR = 5.14; 95% CI = 2.28–11.56), were identified as independent risk factors of COVID-19 mortality, while no significant association was detected regarding HDL-C [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…2. One risk factor of mortality in COVID-19 patients is the age, 2 and in this study, a stratified randomisation of age has not been done, the mean age of the groups was 67.3 years and 60.1 years, respectively.…”
Section: Comment On 'Comparison Of Losartan and Amlodipine Effects On The Outcomes Of Patient With Covid-19 And Primary Hypertension: A Rmentioning
confidence: 92%